PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA PEMBELAJARAN TEKS EKSPOSISI - Riyan, Muhamad (Diksi, 2021)
Learning media is important for the continuity of learning activities so that these activities jave variations that make students not bored. One of them is with android-based learing media. The android-based learning media is form of alignment in the field of education with advances in the field of technologu. This study aims to produce android-based learning media as a form of learning variation in exposition texts. In addition, this study also aims to see student responses to android-based learning applications. This research method uses a qualitative descriptive method with interview techniques. The object of this research is an application that is organized according to the subject matter and also a review of this android-based learning application. The results of this study indicate that this android-based learning media application has good feasibility to be used as a variation of new learning media in Indonesian lessons.Keywords: Media, learning, android, text, exposition